Pregnancy and alcohol misuse. (30th March 2009) - Guerrini, Irene; Jackson, Siobhan; Keaney, Francis
Abstract : How does alcohol misuse affect pregnancy and babies' outcomes, and how is the problem managed in pregnant women?